T-cell and natural killer-cell lymphomas An update based on the 2008 WHO classification (Hematology Meeting Reports, 2009)
Mature T-cell and NK-cell neoplasms are relatively uncommon, accounting for less than 10% of all non-Hodgkin’s lymphomas on a worldwide basis. The most common subtypes of mature T-cell lymphomas are peripheral T-cell lymphoma, unspecified (PTCL-U) and anaplastic large cell lymphoma (ALCL), ALK+. T-cell and NK-cell lymphomas show significance variations in incidence in different geographical regions and racial populations; relative incidence figures are also influenced by variations in B-cell lymphoma prevalence. Functional approaches to the classification of T-cell lymphomas relate the tumor cells to the innate or adaptive arms of the immune system. The adaptive immune system is functionally complex and includes naïve, effector (regulatory and cytotoxic), and memory T-cells. CD4+ T-cells are primarily regulatory, acting via cytokine production, while CD8+ (and double negative) T-cells are primarily cytotoxic. Most lymphomas of the adaptive immune system are nodally-based and occur in adults. The innate immune system is a more primitive type of immune response. Lymphomas with these properties are typically extranodal, affecting mucosal associated sites where the innate defense system plays an important role. T-cell lymphomas in children more closely relate to the innate immune system. Recent studies have begun to dissect out the T-cell lymphomas and relate them to specific cell types. For example, angioimmunoblastic T-cell lymphoma (AILT) has features of the TFH cell of the germinal center, which provides help to B-cells. In contrast, the cells of ATLL express markers of Treg cells, which suppress immune reactions. These observations help to explain the clinical features of these lymphoma subtypes. ALCL, ALK+, has many unique features, and despite the dedifferentiated appearance and phenotype of the tumor cells, has a relatively good prognosis. Current concepts consider ALCL, ALK– to be unrelated to ALCL, ALK+, but also distinct from PTCL, unspecified.